Variation in the saccharide lectin binding pattern from different isolates of Tritrichomonas foetus - Doumecq, María Laura (2014)
Tritrichomonas foetus (T. foetus) is the causal agent of bovine tritrichomonosis (BT), a venereal disease that causes significant economic losses in the bovine livestock industry. The structural organization of T. foetus presents a cell membrane, an undulating membrane which extends along the parasite, three anterior flagella and a recurrent posterior flagellum. The interaction between the superficial glycoconjugates of the parasite and the host cell is one of the most relevant pathogenic mechanisms. In the present study, we analyzed the saccharide pattern through lectincytochemistry of the cell membrane, undulating membrane, cytoplasm and flagella of 28 isolates of T. foetus. Lectins that labeled most of the isolates were WGA, Con-A, RCA-I, LCA, GS-II and PHA-E showing the presence of D-mannose, D-glucose, N-acetylglucosamine and sialic acid. On the other hand, no labeling was observed in any of the structures with VVA, STA, LEA, Jacalin, GS-I, SJA, PHA-L, DSA, and weak labeling was observed with DBA, PNA, SBA and UEA I, showing therefore a low expression of N-acetylgalactosamine, L-fucose and galactose. In addition, GS II labeled in a granular pattern when lectincytochemistry was positive, whereas LCA strongly labeled the membranes and weakly the cytoplasms. The labeling variations observed among the isolates analyzed in the present work, could be related to differences in the pathogenic behavior of the isolates.